2011
DOI: 10.1007/s00601-011-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

The 4He Trimer as an Efimov System

Abstract: We review the results obtained in the last four decades which demonstrate the Efimov nature of the 4 He three-atomic system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 95 publications
5
39
0
Order By: Relevance
“…The excited state has one node in the hyperradial coordinate, indicating a vibrational excitation that is reminiscent of a breathing mode in classical tri-atomic molecules. Our calculations, shown by the green and red lines in Figure 1A, conclude -in agreement with earlier works (4,10,(13)(14)(15)(16) -that an artificial strengthening of the pair interaction (see the right pointing arrow above Figure 1A) renders the excited state of the helium trimer less strongly bound with respect to the dimer, thus confirming the Efimov character of the trimer state. This character is further supported by the appearance of a 3 second Efimov state upon an artificial weakening of the true two-body He-He potential (dashed black line labeled "2nd ES" in Figure 1A).…”
Section: One Sentence Summarysupporting
confidence: 91%
“…The excited state has one node in the hyperradial coordinate, indicating a vibrational excitation that is reminiscent of a breathing mode in classical tri-atomic molecules. Our calculations, shown by the green and red lines in Figure 1A, conclude -in agreement with earlier works (4,10,(13)(14)(15)(16) -that an artificial strengthening of the pair interaction (see the right pointing arrow above Figure 1A) renders the excited state of the helium trimer less strongly bound with respect to the dimer, thus confirming the Efimov character of the trimer state. This character is further supported by the appearance of a 3 second Efimov state upon an artificial weakening of the true two-body He-He potential (dashed black line labeled "2nd ES" in Figure 1A).…”
Section: One Sentence Summarysupporting
confidence: 91%
“…As X increases, the states that disappear are Efimov states while any states that remain are normal states [15,16,25], For the 7Li4He2 system, it is interesting to adjust Li-He interaction through X to make the relevant two-body binding energy in the range of the newly reported experiment value [27], Through the calculations, we can identify whether, within a realistic range of variation of X, states having Efimov characteristics would be found.…”
Section: Efimov Character For the Excited Statementioning
confidence: 96%
“…States w ith Borrom ean character are w ell established in nuclear physics, but Efimov states have not been found. So far the m ost prom ising m olecular system for the Efimov effect is the helium trim er w hich has been predicted to have two bound states and the excited state has Efim ov nature [15][16][17], However, the expectation has not been confirm ed by the experim ents on m olecular beam s [18,19]. Besides the well studied helium trim ers, there is also grow ing interest in the study o f van der W aals m olecules H e2 X (X = alkali-m etal atom ), w hich are w eakly bound and may also exhibit Efimov states naturally [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, according to aforesaid the atoms in quantum liquid are delocalized and thus nothing prevents them from getting involved into multiple-body interactions where the multiplicity can vary from two to the total number of atoms in the system. An example of multi-body (three and more) interactions being very important for forming bound states of bosons at low temperatures is the Efimov state [23,24] which has been experimentally observed in helium [25], a recent review can be found in [26].…”
Section: Collective Variable Theorymentioning
confidence: 99%